Artifacts, Tools and Generalizing Usability Test Results - Reijonen P; Tarkkanen K (Switzerland, 2025)
Usability testing has gained a rather stable status as a method for usability evaluation even though it has both low reliability and validity. The sources of result variance are well acknowledged among researchers and practitioners. However, the validity problem has not been explicated or exemplified although it is frequently discussed in the literature how the results of usability tests should be interpreted and to what extent results are generalizable. We employ Activity Theory and a case example to argue that the validity problem is mainly caused by the fact that what we are testing are artifacts and what people are using in their real life activities are tools and these two entities are qualitatively different. Basing on our analysis, the effects of the reliability and validity problems on the application of usability testing and its role as one of the tools in the design process are discussed.
Nordic Contributions in IS Research: 6th Scandinavian Conference on Information Systems, SCIS 2015, Oulu, Finland, August 9-12, 2015, Proceedings